2018
DOI: 10.37380/jisib.v8i2.319
|View full text |Cite
|
Sign up to set email alerts
|

Measuring public acceptance with opinion mining: The case of the energy industry with long-term coal R&D investment projects

Abstract: New Web 2.0-based technologies have emerged in the field of competitor/marketintelligence. This paper discusses the factors influencing long-term product development,namely coal combustion long-term R&D/Carbon Capture and Storage (CCS) technology, andpresents a new method application for studying it via opinion mining. The technology marketdeployment has been challenged by public acceptance. The media images/opinions of coal powerand CCS are studied through the opinion mining approach with a global machine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…It includes that the literature as well as the study participants rarely distinguish between different types of capture technologies or ways of utilization. Low levels of public knowledge have been confirmed by recent surveys in a variety of countries 7,8 as well as by (social) media analyses, which revealed that the discussion mainly takes place in expert circles 9,10 . In comparative studies, CCU, that is, scenarios that foresee some kind of utilization of the captured CO 2 , seems to be perceived more positively than CCS 8,11,12 and perceptions of geological storage tend to be the most critical part of the CCUS chain 13 .…”
Section: Social Acceptance Of Ccusmentioning
confidence: 95%
See 1 more Smart Citation
“…It includes that the literature as well as the study participants rarely distinguish between different types of capture technologies or ways of utilization. Low levels of public knowledge have been confirmed by recent surveys in a variety of countries 7,8 as well as by (social) media analyses, which revealed that the discussion mainly takes place in expert circles 9,10 . In comparative studies, CCU, that is, scenarios that foresee some kind of utilization of the captured CO 2 , seems to be perceived more positively than CCS 8,11,12 and perceptions of geological storage tend to be the most critical part of the CCUS chain 13 .…”
Section: Social Acceptance Of Ccusmentioning
confidence: 95%
“…Low levels of public knowledge have been confirmed by recent surveys in a variety of countries 7,8 as well as by (social) media analyses, which revealed that the discussion mainly takes place in expert circles. 9,10 In comparative studies, CCU, that is, scenarios that foresee some kind of utilization of the captured CO 2 , seems to be perceived more positively than CCS 8,11,12 and perceptions of geological storage tend to be the most critical part of the CCUS chain. 13 A few studies have taken a more differentiated view into certain potential application cases of CCUS.…”
Section: State Of Researchmentioning
confidence: 99%
“…The advantage is that the approach is semi-supervised, and works even with partly labeled data. Nuortimo [29] studies social media data from multiple platforms to understand public reactions for a system called Case Carbon Capture and Storage, to control carbon dioxide emissions. Results show that the overall reactions are positive.…”
Section: Related Workmentioning
confidence: 99%
“…Within this context, social media is a novel source of information and an up-todate tool for monitoring public opinion in human-nature interactions [13,14]. Analysis of citizens' interests through social media can be implemented through various means, including smart city [15][16][17], traffic [18][19][20], and energy [21]. Several types of social media have been used for this purpose, and one of the most common is Twitter.…”
Section: Introductionmentioning
confidence: 99%